Final years business pitching: a gateway to entrepreneurial success / Farhana Fakhira Ismail - Ismail, Farhana Fakhira (Faculty of Pharmacy, 2024)
The business pitching event for our final-year students is the ultimate manifestation of their hard work and creativity, serving as a platform to showcase their entrepreneurial skills and innovative ideas. As an integral component of the curriculum, this event provides the students with an opportunity to showcase their business ideas to a panel of community pharmacy experts and faculty members. The event is designed to simulate a real-world business environment, where students must not only demonstrate their understanding of business fundamentals but also their ability to effectively communicate and sell their ideas.